Designing visualisations containing search engine results for novices - Olsson, Simon (My University, 2015)
Designing SEO visualisations and furthermore for novices is a small research area. Not much has been done considering this subject concerning thorough research. The thesis aims to increase knowledge in this area. Furthermore, it is in the interest of the thesis to create a tool which will make SEO data more accessible to novices and that can aid in their seeking of information regarding this area. Several prototypes and design iterations are conducted in order to create a combination of visualisations and representations that will result in the proposed tool. The thesis proposes a design suitable for presenting SEO data to novices. Furthermore, heuristics are discerned and explored in order to establish a set of guidelines concerning core values permeating SEO visualisations aimed at novices. Furthermore, a user study is conducted that suggests the validity of the final design and the proposed heuristics.
Keywords: Människa-datorinteraktion (interaktionsdesign); Human Computer Interaction